Topology generation and optimization of boundary cable nets for the mesh reflector antenna. (15th February 2021) - Yuan, Pengfei; He, Baiyan; Zhang, Lianhong; Jiang, Hang; Nie, Rui; Ma, Xiaofei
Highlights: A topology description and generation method of boundary cable nets is proposed. Three criteria are given to reduce potential boundary cable net topologies. A parameterized pretension design algorithm for mesh reflector antennas is developed. The optimized boundary cable net topology can ensure better tension uniformity. Abstract: The mesh reflector antenna is an ideal large deployable structure for on-orbit service. Surface accuracy and tension uniformity are two important performance indicators of it. The cable net topology, especially boundary cable net topology has great effects on the tension uniformity and also surface accuracy. The boundary cable net topology can vary with the design parameters and supporting truss. Finding the most suitable boundary cable net topology from a large number of potential topologies is a challenging task. At present, topology generation considered both the surface accuracy and tension uniformity is seldom studied. In this paper, the boundary cable net topology generation and optimization method (BGO) which can be applied for different mesh reflector antennas is proposed. Firstly, a generalized topology description method is developed based on the concepts of graph and adjacency matrix in graph theory. Secondly, three criteria are proposed according to the common sense in the generation of potential boundary cable net topologies. Thirdly, the topology optimization strategy setting the tension uniformity as the optimization objective is proposed based on the equilibrium matrix method. Lastly, numerical examples are given, and the results show that with the optimized boundary cable net topologies, better tension uniformity is achieved.